FELINE PANCREATITIS: CAUSES AND DIAGNOSTIC METHODS - Carvalho Meireles Azevedo, Emille; Oliveira Porto, Larissa; Lopes Braga Silva, Dhoglas; Novaes Chaves, Renato (Journal of Interdisciplinary Debates, 2023)
Introduction: The pancreas is in the cranial abdomen with its left lobe positioned between the greater curvature of the stomach and the transverse colon. Its diseases occur frequently, being underdiagnosed due to the nonspecificity of clinical signs and the difficulty of access to the organ through diagnostic imaging, biopsy, and the lack of specific clinicopathological tests. Objective: To verify the main predisposing factors and identify the cause of this disease in felines, through an integrative review. Methodology: This is an integrative review, based on 5 scientific articles, published between the years 2017 to 2022, in the MEDLINE, LILACS, SciELO, VETINDEX, DeepDyve and Google Scholar databases. Data analysis through the collection of information and description of the main data found. Results: Diseases of the exocrine pancreas occur frequently, so pancreatitis refers to inflammation caused by the self- digestion of this organ by secreted pancreatic enzymes that are activated within acinar cells due to a failure of the host’s defense mechanism, which leads to a systemic and local lesion, occurring in conjunction with the activity of pancreatic enzymes and inflammatory mediators such as kinins and free radicals. Final considerations: The diagnosis of the disease is difficult to occur due to the nonspecificity of clinical signs and exams, the treatment of pancreatitis aims to reduce pancreatic activity without causing further damage to the pancreas and adjacent organs and to treat the disease itself since the cause of this is rarely identified.